Natura (nie)odzyskana. Pan Knuta Hamsuna - Kruszelnicki, Michał (Przestrzenie Teorii, 2018)
The Norwegian novelist Knut Hamsun’s outstanding early novel Pan. From Lieutenant Thomas Glahn’s Papers (1894) is often acknowledged as a manifestation of the specificity and profundity of Hamsun’s perception of nature. Contrary to the prevailing opinion, I argue that the novel’s main protagonist cannot be simply seen as the happily fulfilled “man of nature” for whom he wishes to pass. In a critical dialogue with the post-Romantic interpretations of Pan and drawing on some classic philosophical traditions (i.e. Rousseau, Schiller) as well as the modern Norwegian scholarship, I explore the psychological dimension of Hamsun’s masterpiece and present Glahn as an individual who attempts to erase or at least mystify within a personalized narrative the conflict between the objective world and his subjective perception of reality. This predicament seems essential to understanding Glahn’s character and ipso facto Hamsun’s less obvious position in the philosophical debate on the essence of modernity conceived as “Disenchantment”. By carefully following Glahn’s narratives centered on his experience of nature, I reveal their artificial and simulating character. Such a reading allows me to argue that Hamsun’s Pan concurs in a subtler language of literature with the philosophical acknowledgement, dating back to Rousseau, of the impossibility of the individual’s return to the pre-modern time, as if to the realm of original, transcendental sense and immediacy of our experience of the world. The horizons of the modern – perhaps suffice to say: mature? – historicized and highly reflexive consciousness cannot be transgressed; the Romantic sensitivity, in its naïve search for the authentic experience of nature as a source of the self and the sense, can only regain it in discourse, which amounts to positing nature as a beautiful appearance and thus compensating for one’s dramatic feeling of alienation from nature and being conceived of as a metaphysical “wholeness”.